GE_GERICHTE P/2114/2011 vom 25. März 2011 - GE Cour de justice (2011)
; DÉTENTION PROVISOIRE ; RISQUE DE RÉCIDIVE ; SUBSTITUTION(OBLIGATION) ; ADMINISTRATION DES PREUVES ; COMPLÉMENT | CPP 221; CPP.237